A Participatory Action Research (PAR) exploratory initiative for psychosis recovery and resilience. Issue 2 (3rd April 2021) - Thai, Helen; Sharif, Noor; Patrick, Kevin; Meldrum, Chelsea; Gamble, Tyrone; Robertson, Carrie; Wright, Nicola; Fogl, Tomas; Webb, Amy; Tutino, Jessica; Bahl, Nancy; O'Brien, Bronwyn; et al.
ABSTRACT: Although treatments for schizophrenia and psychosis have improved significantly over time, many clients still experience social disparities, such as poverty, unemployment, social network strain, and barriers to community supports, that can negatively impact clinical outcomes and perpetuate the cycle of illness. Research is needed to help better understand and address these concerns. Conventional research models typically do not seek to involve those who are most affected and impacted by research outcomes (i.e., people with lived experience) in developing solutions to address the social concerns that they face. The PAR pilot project was launched to explore and examine the impact of including people with lived experience of psychosis as part of the program development, research process and team, whereby decision-making power and empowerment are shared. The PAR Co-Design Team was comprised of people with lived experience, Psychology students, and clinicians. Collaboratively, the Team prepared and presented two workshops and a poster at the 2019 World Hearing Voices Congress. Qualitative feedback reveals that PAR can be effective to foster client well-being and recovery as well as facilitate clinician learning through social inclusion, meaning-making, and empowerment. However, evaluative improvements are needed to better understand the impact of this practice for all.